# Posts by Bosnian

Total # Posts: 2,671

Maths
Volume of a cube side 3 cm = 3 ^ 3 = 27 cm ^ 3 Volume of a cube side 1 / 2 cm = ( 1 / 2 ) ^ 3 = 1 / 8 cm ^ 3 27 / ( 1 / 8 ) = 27 * 8 = 216 cubes OR 3 cm / ( 1 / 2 ) cm = 6 6 ^ 3 = 216 cubes

Math(precalc)
4 ^ ( 4 x - 3 ) = 3 ^ ( 9 x - 6 ) ( 2 ^ 2 ) ^ ( 4 x - 3 ) = 3 ^ ( 9 x - 6 ) Take the natural logarithm of both sides and use the identity: log ( a ^ b ) = b * log a log 2 ^ 2 = 2 * log ( 2 ) log [ ( 2 ^ 2 ) ^ ( 4 x - 3 ) ] = log ( 2 ^ 2 ) * ( 4 x - 3 ) = 2 * log ( 2 ) * ( 4 x...

Math
If your figure a circle then: C = d * pi C = 23 * 3.1415926535 = 72.2566310305 ft approximate = 72 ft

calculus
Correct answer? Quotient Rule for Derivatives: [ f ( t ) / g ( t ) ] ´ = g ( t ) * f ´( t ) - f ( t ) * g ´( t ) / g ( t ) ^ 2 In this case g ( t ) = c + t so: w ( t )´ = [ ( c + t ) * f´( t ) - f ( t ) * ( c + t )´ ] / ( c + t ) ^ 2 = [ ( c...

Maths
g = numbers of girls b = number of boys There are 15 more boys than girls mean: b = g + 15 The ratio of the number of girls to the number of boys in a sports club is 3:6 mean: g / b = 3 / 6 3 / 6 = 1 / 2 so: g / b = 1 / 2 Replace b = g + 15 in this equation. g / ( g + 15 ) = 1...

Math Plz help ASAP
1) p = 3 f 2) 2 x + 3 3) -7 x 4) y = 3 x for x = 0 , y = 3 * 0 = 0 for x = 1 , y = 3 * 1 = 3 for x = 2 , y = 3 * 2 = 6 for x = 3 , y = 3 * 3 = 9 0 , 3 , 6 , 9 Answers: B C A [ if y = -7 x ] B

math 1
9 x - 4 y = - 3 Multiply both sides by 8 72 x - 32 y = - 24 8 x - 3 y = - 1 Multiply both sides by 9 72 x - 27 y = - 9 72 x - 32 y = - 24 - 72 x - 27 y = - 9 ___________________ - 32 y - ( - 27 y ) = - 24 - ( - 9 ) - 32 y + 27 y = - 24 + 9 - 5 y = - 15 Divide both sides by - 5...

math 1
Correct answer. But 82=-82 Isn't correct. Least Common Denominator of 6 and 8 is 24, not 48. 6 x + 8 y = 4 Multiply both sides by 4 24 x + 32 y = 16 8 x - 3 y = 19 Multiply both sides by - 3 - 24 x + 9 y = - 57 24 x + 32 y = 16 + - 24 x + 9 y = - 57 ___________________ 41 ...

math
a) x = numbers of marbles when the container is filled ( 3 / 5 ) x = 45 Multiply both sides by 5 3 x = 5 * 45 3 x = 225 Divide both sides by 3 x = 225 / 3 x = 75 b ) 2 / 5 marbles are needed to completely fill. ( 2 / 5 ) * 75 = 2 * 75 / 5 = 150 / 5 = 30 OR a) 3 / 5 = 2 * 3 / 2...

math 1

Math
1. ? 13 ^ 2 = 13 3 ? 13 ^ 2 = 3 * 13 = 39 2. ( 2 / 3 ) ^ 5 = ( 2 / 3 ) ^ 4 * ( 2 / 3 ) = [ ( 2 / 3 ) ^ 2 ] ^ 2 * ( 2 / 3 ) ? ( 2 / 3 ) ^ 5 = ? [ ( 2 / 3 ) ^ 2 ) ^ 2 ] * ? ( 2 / 3 ) = ( 2 / 3 ) ^ 2 * ? ( 2 / 3 ) = ( 4 / 9 ) * ? ( 2 / 3 ) = 4 * ? ( 2 / 3 ) / 9 = 4 * ? 2 / 9 * ? 3

Math
A. Flat doesn't change 2 changes with x y = 2 x + 5 B. y-intercept is a point on the graph where x is zero. y = 2 * 0 + 5 = 0 + 5 = 5 x = 0 , y = 5 x-intercept is a point on the graph where y is zero. 2 x + 5 = 0 2 x = - 5 x = - 5 / 2 = - 2 .5 x = - 2.5 , y = 0 Draw ...

Math
x = first number x + 1 = second number 1 / x + 1 / ( x + 1 ) = 17 / 72 [ 1 * ( x + 1 ) + 1 * x ] / [ x * ( x + 1 ) ] = 17 / 72 [ ( x + 1 ) + x ] / [ x * x + x * 1 ) ] = 17 / 72 ( 2 x + 1 ) / ( x ^ 2 + x ) = 17 / 72 Multiply both sides by 72 72 * ( 2 x + 1 ) / ( x ^ 2 + x ) = ...

math
2 ^ ( - 3 x ) = 1 / 2 ^ ( 3 x ) = 1 / 4 so: 2 ^ ( - 3 x ) = 1 / 4 1 / 2 ^ ( 3 x ) = 1 / 4 Take reciprocials of both sides: 2 ^ ( 3 x ) = 4 2 ^ ( 3 x ) = 2 ^ 2 Take the logarithm base 2 of both sides 3 x = 2 Divide both sides by 3 x = 2 / 3

Calculus
A constant factor within an integrand can be separated from the integrand and multiplied by the integral. In this case: integral [ ( 1 / 2 ) * e ^ ( t / 2 ) dt ] = 1 / 2 integral e ^ ( t / 2 ) Substitute: u = t / 2 du = dt / 2 Multiply both sides by 2 2 du = dt dt = 2 du 1 / 2...

math
a = first numbner b = second number b = 3 a a + b = 20 a + 3 a = 20 4 a = 20 Divide both sides by 4 a = 5 b = 3 a = 3 * 5 = 15 The two numbers: 5 and 15

Algebra
3 n ^ 2 + 21 n = 3 n * n + 3 n * 7 = 3 n ( n + 7 ) 6 n ^ 2 + 18 n = 6 n * n + 6 n * 3 = 6 n ( n + 3 )

math
52 % of 825 = ( 52 / 100 ) * 825 = 52 * 825 / 100 = 42900 / 100 = 429 boys When more boys joined the school numbers of boys will be: 429 + x total number of pupils will be 825 + x ( 429 + x ) / ( 825 + x ) = 64 % = 64 / 100 = 0.64 ( 429 + x ) / ( 825 + x ) = 0.64 Multiply both...

Math
The ratio: 5 : 3 : 2 5 + 3 + 2 = 10 5 / 10 = 0.5 = 50 % peanuts 3 / 10 = 0.3 = 30 % walnuts 2 / 10 = 0.2 = 20 % cashews 0.3 * 12 = 3.6 Answer c

calculus
v = ds / dt = s´(t) = 1/ ( 1 + t ) ^ 2

math
12 days / 10 days = 12 / 10 = 1.2 1.2 * 20 men = 24 men

math
t1 = 75 = results of the first test t2 = 81 = results of the secondt test t3 = 88 = results of the third test t4 = 92 = results of the fourth test t = results of the fifth test average of 5 test a = ( t1 + t2 + t3 + t4 + t ) / 5 Nick needs a test average of 80 or better mean...

math
N = Present Nancy ages C = Present Cathy ages Nancy is 3 times as old as Cathy mean: N = 3 C In seven years Nancy will be N + 7 yrs old , Cathy will be C + 7 yrs old In seven years, she will be ten years older than Cathy Mean: N + 7 = C + 7 + 10 N + 7 = C + 17 Subtract 7 to ...

Math
26

Algebra
Every odd integer can be written in the form 2 k + 1 So your first integer is a1 = 2 k + 1 Second integer is a2 = first integer + 2 = a1 + 2 = 2 k + 1 + 2 = 2 k + 3 Third integer is a3 = second integer + 2 = a2 + 2 = 2 k + 3 + 2 = 2 k + 5 Product of the first integer and the ...

algebra
x = 5 y = - 2 x + 9 = - 2 * 5 + 9 = - 10 + 9 = - 1 x = 5 , y = - 1

algebra
2 x + y = 9 Subtract 2x to both sides 2 x + y - 2 x = 9 - 2 x y = 9 - 2 x y = - 2 x + 9 Now put x values in this formula x = - 3 y = - 2 x + 9 = - 2 * ( - 3 ) + 9 = 6 + 9 = 15 x = - 3 , y = 15 x = 1 y = - 2 x + 9 = - 2 * 1 + 9 = - 2 + 9 = 7 x = 1 , y = 7 x = 4 y = - 2 x + 9...

math
Correction y > ( 99 / 13 ) / - 15 y > - 99 / 13 * 15 y > - 33 * 3 / 13 * 5 * 3 y > - 33 / 13 * 5 y > - 33 / 65

math
If ?15/9y < 11/13 mean: ?( 15 / 9 ) y < 11 / 13 then multiply both sides by 9 - 15 y < 99 / 13 Divide both sides by - 15 When you multiply or divide both sides of an inequality by a negative number, you must reverse the direction of the inequality. y > ( 99 / 13...

math
J = Justin's age S = Sam's age Justin is 3 years older then Sam mean: J = S + 3 Justin’s age in 2 years will be twice what Sam’s age was 3 years ago mean: J + 2 = 2 ( S - 3 ) Replace J = S + 3 in this equation. S + 3 + 2 = 2 * S - 2 * 3 S + 5 = 2 S - 6 ...

math
R = L + 6 R + 5 + L + 5 = 2 ( R - 4 + L - 4 ) R + L + 10 = 2 ( R + L - 8 ) R + L + 10 = 2 * R + 2 * L - 2 * 8 R + L + 10 = 2 R + 2 L - 16 Replace R = L + 6 in this equation L + 6 + L + 10 = 2 ( L + 6 ) + 2 L - 16 2 L + 16 = 2 * L + 2 * 6 + 2 L - 16 2 L + 16 = 2 L + 12 + 2 L - ...

maths
25 m

algebra
a = first integer a + 1 = second integer a + 2 = third integer first integer + third integer: a + a + 2 = 16 2 a + 2 = 16 Subtract 2 to both sides 2 a + 2 - 2 = 16 - 2 2 a = 14 Divide both sides by 2 a = 14 / 2 = 7 Three consecutive integers are 7, 8 , 9 7 + 9 = 16

math
x = present age One half of her age two years from now: ( x + 2 ) / 2 One third of her age three years ago: ( x - 3 ) / 3 ( x + 2 ) / 2 + ( x - 3 ) / 3 = 20 Multiply both sides by 2 2 * ( x + 2 ) / 2 + 2 * ( x - 3 ) / 3 = 20 * 2 ( x + 2 ) + 2 * ( x - 3 ) / 3 = 40 Multiply both...

Math
V = L * W * D V = 25 * 10 * 2 = 500 m ^ 3

Ordinary Differential Equation
Straight line in slope intercept form: y = m x + b Differentiate: dy = m dx + 0 dy = m dx dy / dx = m

algebra
1) b = ? ( c ^ 2 - a ^ 2 ) b = ? ( 20 ^ 2 - 15 ^ 2 ) b = ? ( 400 - 225 ) b = ? ( 175 ) b = ? ( 7 * 25 ) b = ? 7 * ? ( 25 ) b = ? 7 * 5 2) c = ? ( a ^ 2 + b ^ 2 ) c = ? ( 9 ^ 2 + 12 ^ 2 ) c = ? ( 81 + 144 ) c = ? ( 225 ) c = 25

math
L1 = Length of 1st piece L2 = Length of 2st piece L3 = Length of 3st piece The 1st piece is 4.25 feet longer than the second piece mean: L1 = L2 + 4.25 The 3rd piece is 2.24 feet longer than the second mea. L3 = L2 + 2.24 L1 + L2 + L3 = 10 ft L2 + 4.25 + L2 + L2 + 2.24 = 10 3 ...

math
Aare you kidding? 78 + 99 = 177 100 - 98 = 2 ( 78 + 99 ) + ( 100 - 98 ) = 177 + 2 = 179

math
13 x ? 6 y = 2 Multiply both sides by 4 52 x - 24 y = 8 3 x ? 4 y = ? 10 Multiply both sides by - 6 - 18 x + 24 y = 60 Now solve system: 52 x - 24 y = 8 - 18 x + 24 y = 60 52 x - 24 y = 8 + - 18 x + 24 y = 60 __________________ 34 x + 0 = 68 34 x = 68 Divide both sides by 34 x...

Math
7 / 10 = 7 * 4 / 10 * 4 = 28 / 40 11 / 20 = 11 * 2 / 20 * 2 = 22 / 40 4 / 5 = 4 * 8 / 5 * 8 = 32 / 40 Smallest to largest: 22 / 40 , 28 / 40 , 32 / 40 11 / 20 , 7 / 10 , 4 / 5

slope intercept, math
The two-point form of a line passing through the points (x1 , y1 ) and ( x2 , y2 ) is given by: y - y1 = [ ( y2 - y1 ) / ( x2 - x1 ) ] * ( x - x1 ) In this case: x1 = 4 , y1 = 7 x2 = - 5 , y2 = - 5 y - y1 = [ ( y2 - y1 ) / ( x2 - x1 ) ] * ( x - x1 ) y - 7 = [ ( - 5 - 7...

math
n = numerator d = denominator A fraction reduces to 2 / 3 when 3 is adding to both its numerator mean: ( n + 3 ) / ( d + 3 ) = 2 / 3 Reduces to 3 / 5 when 1 is added to both its numreator and denominator mean: ( n + 1 ) / ( d + 1 ) = 3 / 5 Now: ( n + 3 ) / ( d + 3 ) = 2 / 3 ...

maths
Replace n = 19 in formula 4 n + 3 4 * 19 + 3 = 76 + 3 = 79

Math (calc)
In an open box you have square base with area a ^ 2 and 4 rectangle with area a * h where: a = length of base h = height of box Volume of box: V = a ^ 2 * h = 12 ft ^ 3 a ^ 2 * h = 12 Divide both sides by a ^ 2 h = 12 / a ^ 2 Area of an open box: A = a ^ 2 + 4 a * h A = a ^ 2...

Math
3 / 4

Algebra
0.54 is a rational number = 54 / 100 = 2 * 27 / 2 * 50 = 27 / 50 But if 0.54 mean 0.5454545454 then: 100 * 0.5454545454 = 54.54545454 100 * 0.5454545454 - 0.5454545454 = 99 * 0.5454545454 = 54.54545454 - 0.54545454 = 54 99 * 0.5454545454 = 54 Divide both sides by 99 0....

math
18 / ( 2 / 3 ) = 3 * 18 / 2 = 54 / 2 = \$27

Algebra
1 m = 100 cm 1 cm = 1 m / 100 60.5 / 100 = 0.605 m

College Algebra
x + 2 y = 0 Subtract 2 y to both sides x + 2 y - 2 y = 0 - 2 y x = - 2 y x + 2 y = 0 + x + 3 y + z = 1 + - 4 x - y - z = 23 ___________________ - 2 x + 4 y = 24 - 2 * ( - 2 y ) + 4 y = 24 4 y + 4 y = - 24 8 y = 24 Divide both sides by 8 y = 24 / 8 = 3 x = - 2 y = - 2 * 3 = - 6...

Algebra
12 - 3 = 9 21 - 12 = 9 31 - 21 = 9 The common difference of successive members is 9 This is arithmetic progression. In arithmetic progression: an = a1 + ( n - 1 ) * d In this case: a1 = 3 , d = 9 an = a1 + ( n - 1 ) * d an = 3 + ( n - 1 ) * 9 an = 3 + 9 n - 9 an = 9 n - 6 n = ...

Math
11

math
If the initial term of an arithmetic sequence is a1, and the common difference of successive members is d, then the nth term of the sequence is given by: an = a1 + ( n -1 ) * d In this case: a1 = p , a2 = 2 p + 2 , a3 = 5 p + 3 so a2 = a1 + ( 2 -1 ) * d = p + 1 * d = p + d a2 ...

Finite math
a = adults c = childrens s = students With a full audience: a + c + s = 900 There were half as many adults as children and students combined mean: a = ( s + c ) / 2 Replace this in equation: a + c + s = 900 ( s + c ) / 2 + c + s = 900 Multiply both sides by 2 s + c + 2 c + 2 s...

Basic math
tan ( A + B ) = ( tan A + tan B ) / ( 1 - tan A * tan B ) In this case: A = 2 alpha , B = beta so tan ( 2 alpha + beta ) = [ tan ( 2 alpha ) + tan ( beta ) ] / [ 1 - tan ( 2 alpha ) * tan ( beta ) ] Since the: tan ( 2 alpha ) = 2 * tan ( alha ) / [ 1 - tan ^ 2 ( alpha ) ] put...

(3,4) m = 2 mean x = 3 , y = 4 , m = 2 slope intercept form: y = m x + b 4 = 2 * 3 + b 4 = 6 + b Subtract 6 to both sides 4 - 6 = 6 + b - 6 - 2 = b b = - 2 Now: y = m x + b y = 2 x + ( - 2 ) y = 2 x - 2

Algebra
( x - x1 ) ( x - x2 ) = [ x - ( - 2 ) ] ( x - 3 ) = ( x + 2 ) ( x - 3 ) = 0 Answer c.

Algebra
The n-th term of a geometric sequence with initial value a and common ratio r is given by: an = a * r ^ ( n - 1 ) a is the first term r is common ratio In this case: a1 = a * r ^ ( 1 - 1 ) = a * r ^ 0 = a * 1 = a a2 = a * r ^ ( 2 - 1 ) = a * r ^ 1 = a * r a3 = a * r ^ ( 3 - 1...

Algebra 2
and yes : (base of logarithm)^ log ( x ) = x log 6 (36) = 2 log base (6) (36) = 2 becouse 6 ^ 2 = 36

Algebra 2
log ( x ^ n ) = n * log ( x ) log ( 36 ) = log ( 6 ^ 2 ) = 2 * log ( 6 )

math
If the initial term of an arithmetic progression is a1 and the common difference of successive members is d, then the nth term of the sequence an is given by: an = a1 + ( n -1 ) * d a1 = 5 a100 = a1 + ( 100 - 1 ) * d = - 292 a100 = 5 + 99 d = - 292 5 + 99 d = - 292 Subtract 5 ...

mathematical literacy
( 6 x 3 ) - 4 + 26 ÷ 2 = 18 - 4 + 13 = 14 + 13 = 27

Algebra
2 , 6 , 12 , 20... n = 1 a1 = 2 = 1 + 1 = 1 ^ 2 + 1 = n ^ 2 + n n = 2 a2 = 6 = 4 + 2 = 2 ^ 2 + 2 = n ^ 2 + n n = 3 a3 = 12 = 9 + 3 = 3 ^ 2 + 3 = n ^ 2 + n n = 4 a3 = 20 = 16 + 4 = 4 ^ 2 + 4 = n ^ 2 + n an = n ^ 2 + n

math
2 * 48 * 1 + 2 * ( 40 - 2 ) * 1 = 96 + 2 * 38 = 96 + 76 = 172 cm ^ 2 OR 2 * 40 * 1 + 2 * ( 48 - 2 ) * 1 = 80 + 2 * 46 = 80 + 92 = 172 cm ^ 2 OR New dimensions of a picture : 48 - 2 = 46 cm and 40 - 2 = 38 cm 48 * 40 - 46 * 38 = 1920 - 1748 = 172 cm ^ 2

Maths
l = length w = width P = 2 ( w + l ) If each side is a whole number, then: 1. w = 1 , l = 7 P = 2 ( w + l ) P = 2 ( 1 + 7 ) = 2 * 8 = 16 1 x 7 2. w = 2 , l = 6 P = 2 ( w + l ) P = 2 ( 2 + 6 ) = 2 * 8 = 16 2 x 6 3. w = 3 , l = 5 P = 2 ( w + l ) P = 2 ( 3 + 5 ) = 2 * 8 = 16 3 x ...

algebra
x ^ 2 - 3 x = 4 The x-term coefficient = ? 3 The half of the x-term coefficient = ? 3 / 2 After squaring you have ( ? 3 / 2 ) ^ 2= 9 / 4 x ^ 2 - 3 x = 4 Add 9 / 4 to both sides x ^ 2 - 3 x + 9 / 4 = 4 + 9 / 4 x ^ 2 - 3 x + 9 / 4 = 16 / 4 + 9 / 4 x ^ 2 - 3 x + 9 / 4 = 25 / 4 ...

math
P = x + 2 x - 1 + 2 x + 1 = 40 5 x = 40 Divide both sides by 5 x = 8 cm 2 x - 1 = 2 * 8 - 1 = 16 - 1 = 15 cm 2 x + 1 = 2 * 8 + 1 = 16 + 1 = 17 cm Largest angle = 90° becouse your triangle is right triangle. Use the Pythagorean theorem. The square of the hypotenuse is equal...

Algebra
x ^ 2 * y ^ 2 + x ^ 3 * y ^ 4 = ( 3 x y ) ^ 2 x ^ 2 * y ^ 2 + x ^ 2 * y ^ 2 ( x * y ^ 2 ) = 9 x ^ 2 * y ^ 2 x ^ 2 * y ^ 2 * ( 1 + x * y ^ 2 ) = 9 * x ^ 2 * y ^ 2 Divide both sides by x ^ 2 * y ^ 2 1 + x * y ^ 2 = 9 Subtract 1 to both sides 1 + x * y ^ 2 - 1 = 9 - 1 x * y ^ 2...

integral calculus
My typo. Integrate sin ^ 2 (x) dx = x / 2 - sin (2x) / 4 + C

integral calculus
If (((cos^2(x)*sin(x)/(1-sin(x)))-sin(x)) mean: cos ^ 2 (x) * sin (x) / [ 1 - sin(x) ] - sin (x) then: cos ^ 2 (x) * sin (x) / [ 1 - sin(x) ] - sin (x) = sin (x) * { cos ^ 2 (x) / [ 1 - sin(x) ] - 1 } = sin (x) * { [ 1 - sin ^ 2 (x) ] / [ 1 - sin(x) ] - 1 } = sin (x) * { [ 1...

math
3 x + 2 y = 4 Multiply both sides by 2 6 x + 4 y = 8 2 x - 3 y = 7 Multiply both sides by 3 6 x - 9 y = 21 6 x + 4 y = 8 - 6 x - 9 y = 21 ______________ 6 x - 6 x + 4 y - ( - 9 y ) = 8 - 21 4 y + 9 y = 13 13 y = - 13 Divide both sides by 13 y = - 13 / 13 = - 1 Replace this ...

Linear Algebra
Replace F(x)with y y = 3 x Interchange the variables x = 3 y Divide both sides by 3 x / 3 = y y = x / 3 Replace y with F(x) F(x)= x / 3

math
Where is your list of a points?

math
4:8= 1 / 2 b = boys g = girls g = 24 b = g / 2 b = 24 / 2 b = 12

math connections
Correction. I forget - sign. - 4 n + 7 + 2 n = 1 - 4 n + 2 n + 7 = 1 - 2 n + 7 = 1 Subtract 7 to both sides - 2 n + 7 - 7 = 1 - 7 - 2 n = - 6 Divide both sides by - 2 n = - 6 / - 2 n = 3

math connections
1. x / 4 + 1 = - 5 Subtract 1 to both sides x / 4 + 1 - 1 = - 5 - 1 x / 4 = - 6 Multiply both sides by 5 x = - 6 * 4 x = - 24 2. 6 x + 29 = 5 Subtract 29 to both sides 6 x + 29 - 29 = 5 - 29 6 x = - 24 Divide both sides by 6 x = - 24 / 6 x = - 4 3. - 21 a + 16a = - 5 a 4. 9 a...

elementary school
( 15 / 4 ) / ( 9 / 1 ) = 15 * 1 / ( 4 * 9 ) = 15 / 36 = 3 * 5 / ( 3 * 12 ) = 5 / 12 15 / 4 divided by 9 / 1 = 5 / 12

help with math plz
Suppose your function y is a linear function. Linear equation in slope-intercept form: y = m x + b m = the slope of a linear function = rise / run = change in y / change in x b = y ? intercept = the point where the graph of a linear equation intersect the y-axis y ? intercept ...

HELP ME PLZ MATH
Yes, you are right.

Math
| x - 2 | + 1 = x - 2 + 1 = x - 1 OR | x - 2 | + 1 = - ( x - 2 ) + 1 = - x + 2 + 1 = - x + 3 For vertex you must find point where: x - 1 = - x + 3 x - 1 = - x + 3 Add x to both sides x - 1 + x = - x + 3 + x 2 x - 1 = 3 Add 1 to both sides 2 x - 1 + 1 = 3 + 1 2 x = 4 Divide ...

Math
The total number of football (x) and basketball (y) is 180 mean: x + y = 180 There are 30 more football than basketball mean: x = y + 30 Replace this value in equation x + y = 180 x + y = 180 y + 30 + y = 180 2 y + 30 = 180 Subtract 30 to toth sides 2 y + 30 - 30 = 180 - 30 2 ...

Algebra
1. 4 ( ax + 3 )-3 ax = 25 + 3a 4 * ax + 4 * 3 - 3 ax = 25 + 3a 4 ax + 12 - 3 ax = 25 + 3a 4 ax - 3 ax + 12 = 25 + 3a ax + 12 = 25 + 3a Subtract 12 to both sides ax + 12 - 12 = 25 + 3a - 12 ax = 25 - 12 + 3a ax = 13 + 3a Subtract 3a to both sides ax - 3a = 13 + 3a - 3a ax - 3a...

math
Full circle = 360° For 1 hour small hands move 360° / 12 = 30° 1h to 4h = 3h 3 * 30 ° = 90 °

Calculus
1. f ( x ) = x ^ - 2 = 1 / x ^ 2 f'(x) = lim ? f ( x ) / ?x ?x ->0 ? f ( x ) = 1 / ( x + ?x ) ^ 2 - 1 / x ^ 2 = [ x ^ 2 - ( x + ?x ) ^ 2 ] / [ ( x + ?x ) ^ 2 * x ^ 2 ] = [ x ^ 2 - ( x ^ 2 + 2 x * ?x + ?x ^ 2 ) ] / [ ( x + ?x ) ^ 2 * x ^ 2 ] = ( x ^ 2 - x ^ 2 - 2 x * ?x...

Maths
Your question does not make sense. If the ratio of numerator and denominator is 5:2 = 2.5 is impossible increase the numerator and decrease the denominator and get the ratio 1:4

Algebra
Rewrite your equations: 11 + x = - 15 y Subtract 11 to both sides 11 + x - 11 = - 15 y - 11 x = - 15 y - 11 Add 15 y to both sides x + 15 y = - 15y - 11 + 15 y x + 15 y = - 11 2 x - 5 y = 48 Multiply both sides by 3 2 x * 3 - 5 y * 3 = 48 * 3 6 x - 15 y = 144 Now your system ...

Math fractions
4 + 22 / 15 = 4 + ( 15 + 7 ) / 15 = 4 + 15 / 15 + 7 / 15 = 4 + 1 + 7 / 15 = 5 + 7 / 15 = 5 7/15

Algebra
x ^ 2 - 12 x = - 36 Add 36 to both sides x ^ 2 - 12 x + 36 = - 36 + 36 x ^ 2 - 12 x + 36 = 0 a = 1 , b = - 12 , c = 36 Quadratic Formula : x1/2 = [ - b ± sqroot ( b ^ 2 - 4 a c ) ] / 2 a x1/2 = [ - ( - 12 ) ± sqroot ( ( - 12 ) ^ 2 - 4 * 1 * 36 ) ] / 2 * 1 x1/2...

math
Let 3x be the smallest angle; this will make other angles 5x and 7x. There are 180° in a triangle, so: 3 x + 5 x + 7 x = 180 ° 15 x =180° Divide both sides by 15 x = 180° / 15 x = 12 ° Angles: 3 x = 3 * 12 = 36° 5 x = 5 * 12 = 60° 7 x = 7 * 12 = 84&...

Math
10 / 5 = 2 10 / 5 - ?5 = 2 - ?5

math
- 4 - ( - 15 ) = - 4 + 15 = 11 7 - ( - 4 ) = 7 + 4 = 11 18 - 7 = 11 29 - 18 = 11 d = 11

Math
A = greatest angle B = smaller angle A = B + 18° The sum of the angles in a triangle is 180° 2 A + B = 180° 2 ( B + 18° ) + B = 180° 2 B + 2 * 18° + B = 180° 3 B + 36° = 180° Subtract 36° to both sides 3 B + 36° = 180° 3 B + 36&...

Maths
You must find the least common multiple (LCM) of the positive integers 2 to 10 One way to find LCM's is to use prime factorization: 2 is prime 3 is prime 4 = 2 * 2 = 2 ^ 2 5 is prime 6 = 2 * 3 7 is prime 8 = 2 * 2 * 2 = 2 ^ 3 9 = 3 * 3 = 3 ^ 2 10 = 2 * 5 The LCM of all of ...

Maths
a5 = 3 a2 a12 = 2 a6 + 1 For AP: an = a1 + ( n - 1 ) d a1 = initial term of an arithmetic progression d = common difference of successive members a2 = a1 + ( 2 - 1 ) d a2 = a1 + 1 * d a2 = a1 + d a5 = a1 + ( 5 - 1 ) d a5 = a1 + 4 d a6 = a1 + ( 6 - 1 ) d a6 = a1 + 5 d a12 = a1...

Math
LCM ( Least Common Multiple ) for 8 and 20 = 40 a. 4 / 20 = 4 * 2 / 20 * 2 = 8 / 40 7 / 8 = 7 * 5 / 8 * 5 = 35 /40 Abigail collected more aluminum. b. 8 / 40 + 35 / 40 = 43 / 40 = ( 40 + 3 ) / 40 = 40 / 40 + 3 / 40 = 1 + 3 / 40 = 1.075lb

Algebra 2
A quadratic equation have the standrad form: a x ^ 2 + b x + c R = 290 x ? 0.2 x ^ 2 is quadratic equation: R = ? 0.2 x ^ 2 + 290 x + 0 The vertex of a quadratic parabola is the highest or lowest point, the maximum or minimum. When a < 0 a quadratic parabola has a maximum. ...

Math
n = 1 Denominator = 2 = 2 * 1 n = 2 Denominator = 4 = 2 * 2 n = 3 Denominator = 6 = 2 * 3 n = 4 Denominator = 8 = 2 * 4 n = 5 Denominator = 10 = 2 * 5 Expression for the n-th term: 1 / 2n

Math
The product of two prime numbers is NEVER a prime number becouse that it is a product and therefore has factors.

mathematics
315° = 360° - 45° cos 315° = cos ( 360° - 45° ) cos ( A - B ) = sin A * sin B + cos A * cos B In this case: A = 360° , B = 45° sin A = sin 360° = 0 cos A = 1 sin B = sin 45° = sqroot ( 2 ) / 2 cos B = cos 45° = sqroot ( 2 ) / 2 cos...

Algebra
x = Your number The difference between 5 times a number and 20 equals the sum of the number and 40 mean: 5 x - 20 = x + 40 5 x - 20 = x + 40 Subtract x to both sides 5x - 20 - x = x + 40 - x 4 x - 20 = 40 Add 20 to both sides 4 x - 20 + 20 = 40 + 20 4 x = 60 Divide both sides ...